2013
DOI: 10.1016/j.bpj.2012.11.928
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Assessment of DNA Supercoiling and Relaxation by S. Typhimurium and E. Coli DNA Gyrases

Abstract: Type II topoisomerases maintain DNA topology by regulating the level of supercoiling of chromosomes. DNA gyrase is a unique and highly conserved bacterial Type II topoisomerase which is able to introduce negative supercoils into the genome. Using magnetic-tweezers, we assessed the supercoil generation and relaxation activities of Escherichia coli and Salmonella typhimurium DNA gyrases. Our results indicate that under single-enzyme conditions and 0.6-pN tension, both enzymes relax DNA at similar rates, but Salm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…While both gyrases appear to supercoil DNA in processive bursts, the EC enzyme, which derives from a fast-growing bacterium, supercoils at higher rates. Previous single-molecule work has shown that EC and Salmonella typhimurium gyrase are processive motors and that the Bacillus anthracis enzyme processively relaxes positive supercoils ( 36 , 42 ). The ∼5× faster EC gyrase speed than MTB may relate to the difference in doubling time for their respective host cells in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…While both gyrases appear to supercoil DNA in processive bursts, the EC enzyme, which derives from a fast-growing bacterium, supercoils at higher rates. Previous single-molecule work has shown that EC and Salmonella typhimurium gyrase are processive motors and that the Bacillus anthracis enzyme processively relaxes positive supercoils ( 36 , 42 ). The ∼5× faster EC gyrase speed than MTB may relate to the difference in doubling time for their respective host cells in vivo .…”
Section: Discussionmentioning
confidence: 99%